Finite-time Generalized and Modified Generalized Projective Synchronization between Chaotic and Hyperchaotic Systems with External Disturbances - Shukla, Vijay K. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, two different types of synchronization between different chaotic systems with external disturbances in finite-time have been discussed. Further, chaotic and hyperchaotic systems have synchronized up to a desired transformation matrix. To numerically simulate generalized synchronization T chaotic system and a hyperchaotic system have been considered. In addition, modified generalized projective synchronization has been analyzed theoretically and numerically. Numerical results have shown through graphically and agreed with theoretical analysis.